Monitoring the resistance and baseline susceptibility of Plutella xylostella (L.) (Lepidoptera: Plutellidae) against spinetoram in Tamil Nadu, India. (April 2021) - Tamilselvan, R.; Kennedy, J.S.; Suganthi, A.
Abstract: Diamondback moth, Plutella xylostella (Lepidoptera: Plutellidae), is a destructive cosmopolitan pest that affects cruciferous crops, and insecticides are the major tool used for control. This study aimed to evaluate the insecticide resistance status of P. xylostella collected from ten different locations of Tamil Nadu, India against a diverse group of insecticides used by farmers. The results showed that spinetoram and novaluron were highly toxic to P. xylostella with a resistance ratio of 1.89- to 13.85-fold and 5.01- to 16.93-fold, respectively, compared to a susceptible laboratory population. All field populations exhibited a low to moderate level of resistance against spinosad (2.14- to 21.78-fold), emamectin benzoate (3.74- to 41.26-fold), and indoxacarb (3.42- to 29.37-fold), whereas high levels of resistance were observed against chlorantraniliprole (36.67- to 124.72-fold), flubendiamide (12.66- to 93.63-fold), fipronil (31.99- to 156.24-fold), and cypermethrin (26.97- to174.84-fold). A significant correlation was found between the LC50 values of spinetoram and spinosad ( P  = 0.001). However, no significant correlation (P > 0.05) was observed between spinosyn and other insecticides suggesting a lack of cross-resistance with other groups of insecticides. The synergistic assay showed that the metabolic detoxification mechanisms may not be responsible for P. xylostella resistance against spinetoram. Hence, to prevent the development of resistance in P. xylostella, a combination of insecticides having different mechanisms of action should be used in rotation. Graphical abstract: Image 1 Highlights: Baseline susceptibility of spinetoram to Plutella xylostella is first reported from India. Low to high levels of resistance to eight commonly used insecticides in P. xylostella were determined. Spinetoram exhibit high toxicity towards P. xylostella can be used as an alternate insecticide for resistance management. No cross-resistance was observed between spinetoram and other insecticides except spinosad.